2016
DOI: 10.4049/jimmunol.1600236
|View full text |Cite
|
Sign up to set email alerts
|

Mast Cells Limit the Exacerbation of Chronic Allergic Contact Dermatitis in Response to Repeated Allergen Exposure

Abstract: Allergic contact dermatitis is a chronic T cell-driven inflammatory skin disease that is caused by repeated exposure to contact allergens. Based on murine studies of acute contact hypersensitivity, mast cells (MCs) are believed to play a role in its pathogenesis. The role of MCs in chronic allergic contact dermatitis has not been investigated, in part because of the lack of murine models for chronic contact hypersensitivity. We developed and used a chronic contact hypersensitivity model in wild-type and MC-def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 36 publications
3
49
0
Order By: Relevance
“…Mast cells accumulate in affected tissues of C57BL/6 mice following repeated Ox challenges [ 16 , 27 , 28 ]. We noted a concomitant ~4-fold increase in the abundance of tissue mast cells at day 1 and a ~2-fold increase in total histamine content that persisted through day 21 after 10 labiar Ox challenges.…”
Section: Discussionmentioning
confidence: 99%
“…Mast cells accumulate in affected tissues of C57BL/6 mice following repeated Ox challenges [ 16 , 27 , 28 ]. We noted a concomitant ~4-fold increase in the abundance of tissue mast cells at day 1 and a ~2-fold increase in total histamine content that persisted through day 21 after 10 labiar Ox challenges.…”
Section: Discussionmentioning
confidence: 99%
“…However, inspection of the figures in the 2 papers indicated that, in addition to using different strains of MC‐deficient mice, the 2 groups were studying CHS responses of different severity and duration. This is important, in that Gimenez‐Rivera et al recently reported additional evidence, derived from studies using a different model of CHS tested in both “ Kit ‐dependent” and “ Kit ‐independent” MC‐deficient mice, that MCs can limit the features of this model CHS. Indeed, many different CHS models have been examined with various types of MC‐deficient mice, and the results obtained could be interpreted to indicate that, depending on the circumstances, MCs can enhance, suppress, or have no detectable effects on the features of the tested model …”
Section: Mast Cell‐derived Cytokines Growth Factors and Mitogensmentioning
confidence: 93%
“…However, it now appears that MC IL-10 production also can contribute to immune regulation, at least in cer- COLOUR were studying CHS responses of different severity and duration. This is important, in that Gimenez-Rivera et al 163 In part to address the "controversy" regarding the different conclusions of the studies by Grimbaldeston et al 157 and Dudeck et al, 159 Reber et al 165…”
Section: Il-10mentioning
confidence: 99%
“…By contrast, based on findings in both Kit-mutant and Kit-independent MC-deficient mice, Gimenez-Rivera et al recently reported that MCs can suppress skin inflammation in a new mouse model of chronic CHS (14).…”
Section: Introductionmentioning
confidence: 97%